Process Evaluation of Teaching Critical Thinking About Health Using the Informed Health Choices Intervention in Rwanda: A Mixed Methods Study - Mugisha, Michael; Nyirazinyoye, Laetitia; Ssenyonga, Ronald; Kaseje, Margaret; Lewin, Simon (Global Health: Science and Practice, 2024)
We evaluated the Informed Health Choices secondary school intervention in a cluster randomized trial in Rwanda. The intervention was effective in helping students to think critically about health. In parallel to the trial, we conducted a process evaluation to assess factors affecting the implementation, impacts, and scale-up of the intervention.